Meningkatkan Kinerja Kepala Sekolah Dalam Pengelolaan Administrasi Sekolah Melalui Supervisi Manajerial Di SDK Wairpelit Dan SDI Solot - Yosef Sumardi (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The purpose of this study is to improve the performance of the principal in managing school administration through managerial supervision. The model used in School Action Research is the Kemmis Model which is designed with a cyclical process (cylical) consisting of 4 (four) phases of activities, namely: planning, taking action, observing, and reflecting. These stages continue to repeat until the problem is considered resolved. From the results of data analysis conducted on the implementation of managerial supervision activities in an effort to improve the ability of principals in managing school administration through managerial supervision coaching activities carried out in 2 cycles, it can be concluded that the performance of 2 elementary school principals increased significantly.